Printing continuously graded interpenetrating polymer networks of acrylate/epoxy by manipulating cationic network formation during stereolithography - W. Li; M. Bakhtiary Noodeh; N. Delpouve; J.-M. Saiter; L. Tan; M. Negahban (eXPRESS Polymer Letters)
Ultra-violet (UV) laser assisted stereolithography is used to print graded interpenetrating polymer networks (IPNs) by controlling network formation. Unlike the traditional process where structural change in IPNs is achieved by varying the feeding ratio of monomers or polymer precursors, in this demonstration property is changed by controlled termination of network formation. A photo-initiated process is used to construct IPNs by a combination of radical and cationic network formation in an acrylate/epoxy system. The extent of the cationic network formation is used to control the final properties of the system. Rapid-Scan Fourier Transformation Infrared Spectroscopy (RS-FTIR) is used to track the curing kinetics of the two networks and identify key parameters to control the final properties. Atomic force microscopy (AFM) and differential scanning calorimetry (DSC) confirm the formation of homogenous IPNs, whereas nano-indentation indicates that properties vary with the extent of cationic network formation. The curing characteristics are used to design and demonstrate printing of graded IPNs that show two orders of magnitude variation in mechanical properties in the millimeter scale.